Phytochemical Screening, Antibacterial and Cytotoxic Activity of Dendobium lasianthera J.J.Sm. from Papua - Verena Agustini; Eva S. Simaremare; Elsye Gunawan; Jane Awom; Susan Wopi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
The aims of the study are to evaluate bioactive compounds, antibacterial and cytotoxic potential of D. lasianthera. This orchid grows well all over New Guinea Island as an ornamental plant because of their beautiful flowers. Orchids also known rich of its phytochemical compounds which already used as a traditional medicine in many countries around the world. However, research in pharmacological fields is still limited. In this study, leaves and stem of D. lasianthera were powdered and extracted with ethanol followed by fractionated using n-hexane, ethyl acetate, and ethanol solvent. Extract as well as fraction were tested for phytochemical screening and determined antibacterial activity against Escherichia coli and Staphylococcus aureus using Disc Diffusion Method. Brine Shrimp Lethality Test (BSLT) was used to observe cytotoxic potential of leaves and stem extract and fraction at 10, 50, 100, 250, 500, 750, and 1000 ppm. The results showed that the leaves and stem extract contained tannin and alkaloids, separately. The ethanol extract of D. lasianthera showed 7.35 mm (leaves) and 7.43 mm (stem) inhibition zone against S. aureus Furthermore, the maximum inhibition zone of ethanol fraction of leaves and n-hexane fraction of stem were 8.42 mm and 8.10 mm separately. The LC50 of stem extract and fractions in these study were 699.3 ppm (ethanol extract), 602.1 ppm (ethyl acetate), 329.6 ppm (n-hexane fraction) and 676 ppm (ethanol fraction), whereas for leaves, only ethyl acetate fraction has toxict activity with an average LC50 833.2 ppm. Key words: D. lasianthera; phytochemical screening; antibacterial; cytotoxicity; Papua.